The Role of Women MSME Actors in Increasing Family Income from the Maqashid Shariah Perspective in the East Gegutu Neighborhood - Juairiah, Juairiah; Lenap, Indria Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the role of female MSME actors in increasing family income from a maqashid sharia perspective. This research uses qualitative research methods. The data in this research was obtained from primary data through interviews and observations with female MSME actors in the East Gegutu Environment. Sample determination is carried out using the method random sampling thus obtaining three informants. Data analysis was carried out using a descriptive method with stages of data reduction, data presentation and conclusions. The results of the research show that the role of female MSME actors is very positive in increasing family income and continuing to implement the five main elements that must be maintained in Islam (maqashid sharia), namely hifz ad-din, hifz an-nafs, hifz al-'aql, hifz an-nasl, Andhifz al-mal.